38 Evaluation of an artifact correction algorithm and influence on dose calculation in photon and proton therapy. (December 2018) - Feuillade, J.; Vidal, M.; Duarte, S.; Gautier, M.; Colnard, C.; Peucelle, C.; Maneval, D.; Gérard, A.; Herault, J.
Abstract : Introduction: The Centre Antoine Lacassagne is equipped with a Discovery CT590 RT scanner from GE Healthcare with the smart Metal Artifact Reduction technology (MAR). MAR is a reconstruction algorithm which improves CT data quality in the presence of high Z-metal such as prosthesis or screws for example. This correction of Hounsfield CT number (UH) has potentially an influence on the dose calculation in and around material with high density. The purpose of this study is to evaluate the impact of this reconstruction on photon and proton dose calculation and to propose a methodology to optimize the artifact correction protocol according to the treatment modality. Methods: Phantoms containing different metallic implants (dental sealing and hip prostheses for photontherapy and titanium screw for protontherapy) were built. CT images were acquired with the inserts, and each set of images was reconstructed twice: once with and once without MAR. Different plans were made on the different Treatment Planning System (TPS) according to the technique: Isogray (Dosisoft) with collapsed cone dose calculation for photon and Raystation (Raysearch) with pencil beam and Monte Carlo dose calculation for protontherapy. Dose measurements were made with ionization chambers in the phantom (cylindrical chamber for photon and plane parallel chamber for proton). Then, experimental measurements were compared to the TPS dose calculation for each protocol: - For plan with CT Scan and UH generated with MAR algorithm, - For plans with CT scan and UH without MAR, - For plan with artifact override density in the CT scan with density close to surrounding tissues. Results: The first results show that in protontherapy there is a difference between the doses obtained with or without MAR and therefore it was necessary to adopt 2 different calibration curves. More measurements are in progress. In protontherapy measurements of the equivalent water thickness and the impact on the range in 1D and 2D have to be made. In photontherapy, the observed differences do not significantly affect the dosimetric calculation but play an important role during the contouring phase. Measurements with other dose calculation algorithm have to be made also. Conclusion: This work proposes a methodology to optimize CT protocol and HU-to-density conversion curve when using Metal artifact correction. The methodology has to be adapted according the localization but also the treatment modality and dose calculation algorithm.